Kankanta: Unlocking The Cultural and Educational Significance of Ilocano Folksongs - Bacud, Angeline A.; Bolaron, Genre L.; Sarse, Crestine Mae P.; Tulud, Donnie M.; Ajero, Orfelina M. (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: The subjects of this study were the Ilocano folksongs. This study aimed to collect Ilocano songs, know the worldviews of each song, identify the themes, and determine the different values that are embedded in the songs. Methodology: The researchers aimed to provide a diverse representation of Ilocano culture by collecting 10 Ilocano folksongs specifically songs about relationship. The data were collected online as they were accessible and easy to find. After gathering the necessary data, the researchers sought for English translations of each Ilocano folksong and determined the themes, values, and worldviews in the folksongs. Main Findings: Results showed that Ilocano folksongs contain themes such as love songs, courtship songs, death songs, unrequited love, sorrow, relationship, longing, admiration, and decision-making. Also the results showed that most of the values that are embedded in the songs are about reassurance, loyalty, sincerity, compatibility, thoughtfulness, vulnerability, being considerate, and being meticulous. Novelty/Originality of this study: This study would be a help to various stakeholders of the educational system as well as to the students taking up language and literature related courses for they would benefit and become well-informed of the analyzation of themes, values, and worldviews embedded in the Ilocano folksongs.